Early responses of the STAT3 pathway to platinum drugs are associated with cisplatin resistance in epithelial ovarian cancer - Sheng,W.J. (2013)
Cisplatin resistance remains one of the major obstacles when treating epithelial ovarian cancer. Because oxaliplatin and nedaplatin are effective against cisplatin-resistant ovarian cancer in clinical trials and signal transducer and activator of transcription 3 (STAT3) is associated with cisplatin resistance, we investigated whether overcoming cisplatin resistance by oxaliplatin and nedaplatin was associated with the STAT3 pathway in ovarian cancer. Alamar blue, clonogenic, and wound healing assays, and Western blot analysis were used to compare the effects of platinum drugs in SKOV-3 cells. At an equitoxic dose, oxaliplatin and nedaplatin exhibited similar inhibitory effects on colony-forming ability and greater inhibition on cell motility than cisplatin in ovarian cancer. Early in the time course of drug administration, cisplatin increased the expression of pSTAT3 (Tyr705), STAT3α, VEGF, survivin, and Bcl-XL, while oxaliplatin and nedaplatin exhibited the opposite effects, and upregulated pSTAT3 (Ser727) and STAT3β. The STAT3 pathway responded early to platinum drugs associated with cisplatin resistance in epithelial ovarian cancer and provided a rationale for new therapeutic strategies to reverse cisplatin resistance.